2020
DOI: 10.1111/cmi.13237
|View full text |Cite
|
Sign up to set email alerts
|

Rickettsial pathogen uses arthropod tryptophan pathway metabolites to evade reactive oxygen species in tick cells

Abstract: Reactive oxygen species (ROS) that are induced upon pathogen infection plays an important role in host defence. The rickettsial pathogen Anaplasma phagocytophilum, which is primarily transmitted by Ixodes scapularis ticks in the United States, has evolved many strategies to escape ROS and survive in mammalian cells. However, little is known on the role of ROS in A. phagocytophilum infection in ticks. Our results show that A. phagocytophilum and hemin induce activation of l‐tryptophan pathway in tick cells. Xan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 56 publications
1
30
0
Order By: Relevance
“…In malaria, XA is present in the gut of Anopheles mosquitos and is known to induce gametogenesis of P. falciparum [9]. It has recently been shown that XA supported the growth of a tick-borne pathogen, Anaplasma phagocytophilum, in tick cells by inhibition of tryptophan dioxygenase activity [41]. However, it remains unknown whether this metabolite is present in the tick midgut [10].…”
Section: Discussionmentioning
confidence: 99%
“…In malaria, XA is present in the gut of Anopheles mosquitos and is known to induce gametogenesis of P. falciparum [9]. It has recently been shown that XA supported the growth of a tick-borne pathogen, Anaplasma phagocytophilum, in tick cells by inhibition of tryptophan dioxygenase activity [41]. However, it remains unknown whether this metabolite is present in the tick midgut [10].…”
Section: Discussionmentioning
confidence: 99%
“…Villar and colleagues reported that the presence of A. phagocytophilum leads to overrepresentation of proteins involved in blood digestion and lipid absorption in ticks [ 9 ]. Several other recent studies from our and other groups provide strong evidence that A. phagocytophilum modulates several signaling pathways in ticks for its survival, colonization, and transmission to the vertebrate host [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 93%
“…The observation of inhibition of OATPs that significantly reduced viral replication in tick cells suggests a possible anti-viral role for these molecules ( Taank et al., 2018 ). More recent studies showed that A. phagocytophilum uses tick OATPs and tryptophan pathway metabolism to inhibit build-up of reactive oxygen species that is toxic to bacterial replication ( Dahmani et al., 2020 ). In addition, we noted that A. phagocytophilum regulate tick OATPs through microRNA133 ( Ramasamy et al., 2020 ).…”
Section: Organic Anion Transporting Polypeptides(oatps)mentioning
confidence: 99%